Publishing in the First World War
XIV, 241 p.
Keywords: This book explores the publishing and reading practices formed and changed by the First World War. From an exploration of British and Australian trench journals to the impact of war on the literary figures of the home front, the essays provide new information about the production, circulation and reception of reading matter during this time.